ANTITUMOR DRUGS BASED ON INDOLOCARBAZOL DERIVATIVES - I. P. Kolpaksidi; M. V. Dmitrieva; I. V. Yarosh; I. I. Krasnyuk (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the work is to generalize the literature data on indolocarbazole derivatives with an antitumor activity.Materials and methods. The objects of the study were the preparations based on indolocarbazole derivatives with the antitumor activity. To search for materials on the problem under study, the following search and information as well as library databases were used: ebibrary, PubMed, CyberLeninka, ResearchGate, the State Register of Medicines, clinical trials registries clinline.ru and clinicaltrials.gov. The search for the following words / phrases was performed: indolocarbazoles, indolocarbazole derivatives, staurosporine, rebeccamycin, staurosporine derivatives. The search was conducted from January 11 until March 1, 2021. The compounds with a biological activity which were undergoing or had undergone preclinical and clinical trials, were taken into account. All the materials from 1977 to January 1, 2021, were taken into account.Results. The materials obtained indicate that indolocarbazole derivatives are promising compounds for the creation of anticancer medicinal preparations due to their properties and peculiarities of the action mechanism. These drugs have a selective action due to the targeted interaction with specific molecular targets: kinases (especially protein kinase C and its isozymes), DNA and DNA topoisomerase. To date, many compounds from the class of indolocarbazoles have been synthesized and investigated. They have shown a high antitumor activity in the treatment of systemic and solid tumors. However, despite this, only one MP based on a staurosporine derivative, registered by the TN of Rydapt® (in the USA and EU countries) and Miticaid® (in the Russian Federation), is approved for use in the clinical practice.Conclusion. Thus, the basic data from scientific publications on promising anticancer medicinal preparations based on compounds from the class of indolocarbazoles, have been summarized. The information is provided, in particular, on their molecular structure, the origin, classification, the main representatives of the class, which are at various stages of the research and are approved for use in the clinic.